Implementação de sistema de teste do automatismo e de chave de seleção dos geradores diesel de emergência da subestação de Tucuruí - LOPES, Edson da Silva (2018)
This work aims to focus on the application of automation in electric power substations, through standardization and improved automation of ancillary services cubicle 440/220 volts, system implementation for selecting the mode of operation of diesel generators and a system for automatic test run with a load of diesel generators substation Eletrobras-Eetronorte in Tucuruí, thus solving a critical problem the company with the direct application of the knowledge acquired during their studies. The implementation of this project possou for all phases of data collection (specification and definition of the problem), project generation (initial design, testing and simulations), construction and implementation.